Pigmalión y la estatua: muestras de un tema ovidiano en la poesía española - Cristóbal, Vicente (Cuadernos de Filología Clásica. Estudios Latinos, 2003)
In this article they are picked up and commented poetic Spanish textes (Cetina, Figueroa, Calderón, Porcel, Lloréns, Hierro, Botas and Velaza), that show the pervivence of Ovidian passage about Pygmalion (Met. X243-297).